Long-lived charge carrier generation in ordered films of a covalent perylenediimide–diketopyrrolopyrrole–perylenediimide molecule. Issue 1 (26th September 2014) - Hartnett, Patrick E.; Dyar, Scott M.; Margulies, Eric A.; Shoer, Leah E.; Cook, Andrew W.; Eaton, Samuel W.; Marks, Tobin J.; Wasielewski, Michael R.
Abstract : Self-ordering of covalent electron donor–acceptor building blocks in thin films upon solvent vapor annealing results in a 10 4 increase in photo-generated charge carrier lifetime. Abstract : The photophysics of a covalently linked perylenediimide–diketopyrrolopyrrole–perylenediimide acceptor–donor–acceptor molecule (PDI–DPP–PDI, 1 ) were investigated and found to be markedly different in solution versus in unannealed and solvent annealed films. Photoexcitation of1 in toluene results in quantitative charge separation in τ = 3.1 ± 0.2 ps, with charge recombination in τ = 340 ± 10 ps, while in unannealed/disordered films of1, charge separation occurs in τ < 250 fs, while charge recombination displays a multiexponential decay in ∼6 ns. The absence of long-lived, charge separation in the disordered film suggests that few free charge carriers are generated. In contrast, upon CH2 Cl2 vapor annealing films of1, grazing-incidence X-ray scattering shows that the molecules form a more ordered structure. Photoexcitation of the ordered films results in initial formation of a spin-correlated radical ion pair (electron–hole pair) as indicated by magnetic field effects on the formation of free charge carriers which live for ∼4 μs. This result has significant implications for the design of organic solar cells based on covalent donor–acceptor systems and shows that long-lived, charge-separated states can be achieved by controlling intramolecular charge separation dynamics in well-ordered systems.